Balancing health and socioeconomic impacts: A uniform framework for evaluating non-pharmaceutical interventions - Matjaž Gams; Anže Marinko; Nina Reščič; Aljoša Vodopija; Sophie Vandepitte; Delphine De Smedt; Jana Javornik; Franc Strle; Vito Janko; David Susič; Zoja Anžur; Mitja Luštrek (PLoS ONE, 2025)
This paper introduces a uniform evaluation framework for assessing the effectiveness of past non-pharmaceutical interventions (NPIs) in managing infectious diseases, taking into account the cultural and social differences between countries. The framework enables quantifying and finding the optimal balance of both the health and socioeconomic impacts of NPIs. The aim is to assist policymakers in understanding which NPIs lead to the optimal balance by highlighting unnecessary costs - the costs that could be avoided while maintaining the same infection rates. To assess the extent of unnecessary socioeconomic consequences experienced by a country during a past epidemic of infectious diseases, we use the following approach. First, we develop a model that predicts the number of infections from NPIs in a country. Second, we estimate the socioeconomic costs (SEC) of the NPIs universally for countries included in the study. Third, we develop a model that prescribes the NPI plans with the optimal trade-off between the number of infections and the SEC. Fourth, we create a model that specifically adjusts each country’s SEC. Finally, we provide additional analysis to increase comprehension of the effects of NPIs. Demonstrated through an analysis of COVID-19 pandemic responses in 17 countries, the study offers a systematic presentation of the framework and a concrete examination of the integrated effects of NPIs. It provides insights into interventions’ direct and indirect consequences, offering guidance for future epidemic responses. The framework enables a systematic understanding of the effects of the NPIs applied, acknowledging the national diversity in health measure acceptance and implementation. This allows for fair analysis across countries, identifying and displaying the economic, social, and health-related costs of suboptimal NPI strategies, i.e., unnecessary costs. The framework is applicable for any infectious disease, NPIs, or country, assuming the medical interventions are similar, e.g., timing and amount of vaccination.